Finite-Time Disturbance Observer-Based Sliding Mode Control for a Vehicle Platoon Subject to Mismatched Disturbance - Yiguang Wang; Xiaoyan Zhan; Xiaojie Li; Yongqiang Jiang; Xubin Tang; Yaxuan Wang (Applied Sciences)
The article focuses on the issue of the sliding mode control of a vehicle platoon with matched and mismatched disturbances. A novel finite-time disturbance observer-based sliding mode control scheme is developed to effectively mitigate the adverse impact of disturbances and achieve the control goals of a platoon. As matched and mismatched disturbances might decrease the control performance or even cause the instability of a vehicle platoon, a finite-time disturbance observer (FTDO) is designed to effectively reduce the effects of both types of disturbances. Unlike previous studies, the proposed FTDO in this article has the capability to directly estimate disturbances without the need to know the precise upper bounds of the disturbances. A feedforward compensation term, derived from disturbance estimation, is incorporated into the FTDO-based sliding mode control scheme to solve the issue of the degradation of control performance. The controlled vehicle platoon’s stability is proven through the Lyapunov approach, which means that the control goals of the platoon can be achieved under the developed FTDO-based sliding mode control scheme. Finally, a numerical example is conducted to confirm the efficacy of the developed control scheme.